ANALYSIS OF THE INFLUENCE OF THE IMPLEMENTATION OF QUALITY CONTROL CIRCLE (QCC) AND THE IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT (TQM) ON LABOR PRODUCTIVITY : CASE STUDY AT PT. IRC INOAC INDONESIA - Mursalin (AGUSPATI Research Institute, 2025)
Product quality is one issue in business survival. One of quality strategies using group oriented is known as Quality Control Circle (QCC). The strategy of integrated quality management or Total Quality Management (TQM) can be an option to maintain and improve the quality of the products of a company's business performance. The aim of this research is to analyze the effect of the implementation of QCC and TQM to the labor productivity at PT IRC Inoac Indonesia. The objects observed in this research were employees of PT IRC Inoac Indonesia. The samples studied were 200 employees who have been involved in QCC activities in the 2019 period. The method used for data collection in this study is simple random sampling. The collected data is then further analyzed using Statistical Product and Service Solutions (SPSS) version 24 for windows. This research showes that QCC and TQM has direct effect on the labor productivity. It is known from the coefficient of determination or R2. The amount of R based on the analysis is 0.559. It can be interpreted that the application of QCC and TQM affects labor productivity by 55.9%.